2000
DOI: 10.1097/00006842-200007000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Reported Chronic Insomnia Is Independent of Poor Sleep as Measured by Electroencephalography

Abstract: A history of chronic insomnia does not predict poor EEG sleep. Both chronic insomnia and poor EEG sleep are associated independently with dysphoria, hyperarousal, diminished waking function, and negative subjective sleep quality. Separate arousal and sleep systems are posited to account for these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(86 citation statements)
references
References 24 publications
8
72
0
6
Order By: Relevance
“…Mean value heat and cold pain thresholds for frontal and thenar region, three tests on each side; Mann-Whitney U-test: (*)P = 0.05, *P < 0.05, **P < 0.01, ***P < 0.001. the groups (Table 2). It has been shown that a history of chronic insomnia does not predict poor EEG sleep (23). However, increased slow-wave sleep, as found in the present study among TTH and NSM patients, is one factor that usually indicates better sleep quality (24).…”
Section: Discussionsupporting
confidence: 45%
“…Mean value heat and cold pain thresholds for frontal and thenar region, three tests on each side; Mann-Whitney U-test: (*)P = 0.05, *P < 0.05, **P < 0.01, ***P < 0.001. the groups (Table 2). It has been shown that a history of chronic insomnia does not predict poor EEG sleep (23). However, increased slow-wave sleep, as found in the present study among TTH and NSM patients, is one factor that usually indicates better sleep quality (24).…”
Section: Discussionsupporting
confidence: 45%
“…29,32 Psychological factors such as personality characteristics and mood disorders have been linked to misperception. 9,33,34 Aspects of sleep physiology have been associated with misperception, including hyperarousal, 35 alpha frequency intrusion into slow wave sleep, 11 and the cyclic alternating pattern 12 (but this has not been seen in other work). 36 In addition, in regards to the hyperarousal theory of insomnia, 35 insomnia patients have increased basal metabolic rate and longer sleep latencies during nap studies, among other physiological changes.…”
Section: Perception Of Total Sleep Timementioning
confidence: 99%
“…The disturbance and curtailment of sleep have also been shown to have an impact on metabolic parameters. Insomniacs have been shown to have higher 24-h ACTH levels and cortisol secretion (8,29), elevated urinary catecholamine concentrations (12), and higher sleep-to-awake ratio for metabolic parameters (13). In an experimental study by Spiegel et al (14), sleep debt had an impact on carbohydrate metabolism and endocrine function in young men.…”
Section: Statisticsmentioning
confidence: 99%